2010
DOI: 10.1007/s00774-010-0223-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intravenous zoledronic acid in Chinese women with postmenopausal osteoporosis

Abstract: The aim of this study was to assess the efficacy and safety of a once-yearly zoledronic acid treatment for Chinese women with postmenopausal osteoporosis in Taiwan and Hong Kong. This post hoc subpopulation analysis, from the Health Outcome and Reduced Incidence with Zoledronic Acid One Yearly Pivotal Fracture Trial, enrolled 323 Chinese women with osteoporosis who were randomly given either annual infusions of zoledronic acid or placebo for 3 consecutive years. The incidence of fractures and changes in bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
5
17
2
1
Order By: Relevance
“…A lot of studies have confirmed the benefit of once-yearly ZOL 5 mg. They have demonstrated that ZOL significantly reduces the risk of morphometric vertebral fracture and clinical vertebral fracture, and increases total hip, femoral neck, and trochanter BMD [12,15,22,23]. A few studies have …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of studies have confirmed the benefit of once-yearly ZOL 5 mg. They have demonstrated that ZOL significantly reduces the risk of morphometric vertebral fracture and clinical vertebral fracture, and increases total hip, femoral neck, and trochanter BMD [12,15,22,23]. A few studies have …”
Section: Discussionmentioning
confidence: 99%
“…pointed out that the increasing effect of ZOL on bone mineral density would continue with the increasing time of injections [22,24]. So we supposed that over a two-year period, use of once-yearly ZOL 5 mg, BMD would continue to show improvements.…”
Section: Prace Oryginalnementioning
confidence: 95%
“…However, the reviewers identified only 1 RCT that compared the effect of sex on the response to treatment, 17 and therefore graded as insufficient the evidence from this RCT that calcium and vitamin D3 decreased the risk of fracture in elderly women but not in elderly men. 18 Differences in response to treatment according to race or ethnicity were also evaluated as is common in analyses of population subgroups. Although they found high strength of evidence for decreased vertebral fractures specifically among Asian women treated with raloxifene, these findings were similar to that of U.S. and other international populations.…”
Section: Summary Of Ahrq's Comparative Effectiveness Review Of Treatmmentioning
confidence: 99%
“…Although they found high strength of evidence for decreased vertebral fractures specifically among Asian women treated with raloxifene, these findings were similar to that of U.S. and other international populations. 18,19 The evidence was graded insufficient at the time of this AHRQ review to assess the effect of renal function on the efficacy of therapies except treatment with zoledronic acid, 20 in which impaired renal function reduced the efficacy of zoledronic acid in preventing vertebral (but not hip or other nonvertebral) fractures. 21 …”
Section: Summary Of Ahrq's Comparative Effectiveness Review Of Treatmmentioning
confidence: 99%
“…The Health Outcomes and Reduced Incidence with Zoledronic Acid Once Yearly Pivotal Fracture Trial (HORIZON-PFT) and subsequent sub-analyses have shown a higher incidence of APRs in the Asian populations compared to those in the multinational populations included in the studies [1,3,4]. A sub-analysis of the HORIZON-PFT showed that the incidences of pyrexia and arthralgia in the Chinese population were higher than those in the multinational population, of which 14.2% were Asians (pyrexia, 28.2 vs. 16.1%; arthralgia, 21.5 vs.…”
Section: Introductionmentioning
confidence: 99%